Impact of Co-Channel Interference on Two-Way Relaying Networks with Maximal Ratio Transmission - Aladwani, Awfa; Erdogan, Eylem; Gucluoglu, Tansal (MDPI, 2019)
Amplify-and-forward (AF) two-way relay networks (TWRNs) have become popular to provide spectrally efficient communication when range extension or energy efficiency is needed by utilizing a simple relay. However, their performance can be significantly degraded in practice due to co-channel interference (CCI) which is increasing due to growing number of wireless devices and recent cognitive and non-orthogonal multiple access techniques. With the motivation of improving the performance of AF-TWRNs, the use of maximal ratio transmission (MRT) is investigated to achieve high reliability while requiring low receiver complexity for the relay. First, the signal-to-interference-plus-noise ratio (SINR) expression is formulated and upper bounded. Then, tight lower bound expressions of outage probability (OP), sum symbol error rate (SSER), and upper bound ergodic sum rate (ESR) for each source and for the overall system are obtained. Besides, array and diversity gains are provided after deriving the asymptotic expressions of OP and SSER at high signal-to-noise ratio (SNR). Furthermore, the impact of channel estimation errors on the performance is also included. Finally, Monte Carlo simulation results which corroborate our theoretical findings are illustrated.
Keywords: two-way relay network; maximal ratio transmission; co-channel interference; outage probability; symbol error rate; ergodic sum rate; AMPLIFY-AND-FORWARD; PERFORMANCE ANALYSIS; Computer Science; Engineering; Physics